Dermatomyositis: A Multifaceted Autoimmune Connective Tissue Disorder: Series of Seven Cases - Mrunali Anil Joshi; Pooja Agarwal; Kalgi Baxi; Raju Gisaram Chaudhary; Vama Vijay Patel (Clinical Dermatology Review)
Dermatomyositis is a rare connective tissue disorder having a wide array of characteristic cutaneous and systemic manifestations. There is an established paraneoplastic association of malignancy with dermatomyositis which is seen in adult patients as compared to juvenile (with an increased risk of malignancy in 15%–30% cases in adult dermatomyositis, without any increased risk of association in juvenile dermatomyositis), which can be seen in our case series. There is also a case linking neurological associations of dermatomyositis to generalized tonic–clonic seizures. We discuss the importance of dermatomyositis, as a potential differential diagnosis among the cases presenting with bulbar symptoms such as dyspnea and dysphagia which can be life-threatening.